Akuntansi Sosial: Suatu Tinjauan Mengenai Pengakuan, Pengukuran dan Pelaporan Externalities dalam Laporan Keuangan - Sri Murni (Universitas Muhammadiyah Yogyakarta, Indonesia, 2001)
The purpose of this paper is to conduct a review of the recognition, measurement and reporting of social accounting, especially regarding externalities which includes social benefits and social cost. This article will discuss the introduction, objectives and corporate responsibility, corporate social responsibility, social accounting, ekternalities, problem recognition, measurement and reporting of externalities, social accounting application prospect in Indonesia and conclusions. The conclusion that can be drawn is that the company must carry out social responsibility as a sign of social responsibility towards the environment. And accounting knowledge should be further developed to gain the framework and the basis for the concept of socially-oriented reporting.